Kinetics of neuromuscular fatigue during a 4-km cycling time trial - Azevedo, R.; Milioni, F.; Bertuzzi, R.; Millet, G. Y. (Applied Physiology, Nutrition, and Metabolism, 2018)
The study investigated the kinetics of neuromuscular fatigue (NMF) development during a 4-km cycling time-trial (TT). Eleven males performed in counterbalanced, repeated-measures, and crossover design, three sessions that consisted in the TT until (i) phase I: after the high initial power output stabilizes (800 m), (ii) phase II: before the endspurt (3600 m), and (iii) phase III: complete TT (4000 m) thanks to an avatar that reproduced the same power output. NMF was evaluated with a series of electrically evoked and maximal voluntary isometric contractions (MVC) performed before and immediately after Phase I, Phase I+II, complete TT. It was shown that (i) power output decreased during phase I and there was a drop on MVC (-23%) accompanied by central (-6% for voluntary activation) and peripheral (-39% for peak twitch, Pt); (ii) there was maintenance of the power output during phase II and NMF did not change compared to Post-Phase I; finally, (iii) the power output abruptly increased during the end-spurt of Phase III, which resulted on greater drop on MVC (-34%) and peripheral fatigue (Pt: -57%) when compared to Phase I. In conclusion, NMF appearance is not linear but varies according to the TT phases due to pacing.